If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3a + b) + -1bx = a(x + -2) Remove parenthesis around (3a + b) 3a + b + -1bx = a(x + -2) Reorder the terms: 3a + b + -1bx = a(-2 + x) 3a + b + -1bx = (-2 * a + x * a) 3a + b + -1bx = (-2a + ax) Solving 3a + b + -1bx = -2a + ax Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '2a' to each side of the equation. 3a + b + 2a + -1bx = -2a + 2a + ax Reorder the terms: 3a + 2a + b + -1bx = -2a + 2a + ax Combine like terms: 3a + 2a = 5a 5a + b + -1bx = -2a + 2a + ax Combine like terms: -2a + 2a = 0 5a + b + -1bx = 0 + ax 5a + b + -1bx = ax Add '-1ax' to each side of the equation. 5a + b + -1ax + -1bx = ax + -1ax Reorder the terms: 5a + -1ax + b + -1bx = ax + -1ax Combine like terms: ax + -1ax = 0 5a + -1ax + b + -1bx = 0 Add '-1b' to each side of the equation. 5a + -1ax + b + -1b + -1bx = 0 + -1b Combine like terms: b + -1b = 0 5a + -1ax + 0 + -1bx = 0 + -1b 5a + -1ax + -1bx = 0 + -1b Remove the zero: 5a + -1ax + -1bx = -1b Add 'bx' to each side of the equation. 5a + -1ax + -1bx + bx = -1b + bx Combine like terms: -1bx + bx = 0 5a + -1ax + 0 = -1b + bx 5a + -1ax = -1b + bx Reorder the terms: 5a + -1ax + b + -1bx = -1b + b + bx + -1bx Combine like terms: -1b + b = 0 5a + -1ax + b + -1bx = 0 + bx + -1bx 5a + -1ax + b + -1bx = bx + -1bx Combine like terms: bx + -1bx = 0 5a + -1ax + b + -1bx = 0 The solution to this equation could not be determined.
| N^3-6n^2-4n+24=0 | | 9x-(4x-10)=50 | | 27r^3+125=0 | | 16z^2-40z+25=0 | | ((100x^2)/16)-(4y/49) | | 156.25+5.75x=7x | | 32-12y+y^2=0 | | -64b^2+0z+25=0 | | 25-64b^2=0 | | 13/7(1/2) | | 13/1 | | 8z^2-88z+240=0 | | 7+8v=6+8v | | 3in+X=11in | | X+3in=11in | | 2(x+1)-3(x-1)=5-x | | 2(x+1)-3(x-1)=5-1 | | 3*ln(e)= | | 9(x-10)=-27 | | .20=x^2/85-x | | 5x^3+33x^2-12x+14=0 | | -5/6-(-8/9) | | -7(v+6)=-5v-28 | | (-7/8)^3 | | (x-10)(x+2)=25 | | -10-4x=4x-2 | | 7x^2+2=15 | | 8(y+3)-10y=0 | | 7x-7=-17+6x | | (3pq)/r=12 | | 4x^2-14x-96=0 | | 1/7(7x^2) |